Military Politisation from President Soekarno's Era to President Jokowi - A'dila; Jajang Wawan Setiyawan; Muhammad Fauzi Rizki; Muhammad Rizal Arifin Hidayah (GoResearch - Research & Publishing House, 2022)
This research is a study of how the military has strong influence and power in the political map in Indonesia. This study aims to review the dynamics of the military from the Soekarno regime to Jokowi. The method used is a literature study research method. Methods of collecting library data, reading, and taking notes also analyze research materials and collect secondary data. The results of this study show that during the Soekarno regime the influence of the military in politics had appeared, then during his leadership period the concept of the